ELECTROLYSIS - Musurmanova Nilufar Normukhammadovna; Kabulova Nargiza Akhlisherovna (Journal Park Publishing, 2024)
Electrolysis is a set of redox processes that occur on electrodes placed in a solution or melt of an electrolyte under the influence of a direct electric current applied from an external source. The article describes current aspects.
Keywords: Electrolysis, chemistry, electrode, method.